2018
DOI: 10.1016/j.jvs.2018.07.015
|View full text |Cite
|
Sign up to set email alerts
|

H19 Induces AAA Development and Progression

Abstract: A total of 200 patients with peripheral arterial disease (PAD) were randomized to home-based exercise consisting of on-site sessions for the first month, active exercise, and coaching (99 patients) vs usual care (101 patients) for 9 months. The mean change in walking distance was better in the usual care group than in the exercise group. Conclusion: A home-based exercise program consisting of a wearable activity monitor and telephone coaching did not improve walking performance at 9-month follow-up. These resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Li et al identified mouse lncRNA H19 by RNA sequencing AngII and PPE-induced AAAs in mice. Inhibition of H19 inhibits aneurysm formation in AngII-and PPE-AAA mouse models, lowldlr Yucatan mini pigs, samples from AAAs patients, and low-ldlr Yucatan mini pigs (Li et al, 2018). H19 is markedly elevated in advanced AAAs.…”
Section: H19mentioning
confidence: 90%
See 1 more Smart Citation
“…Li et al identified mouse lncRNA H19 by RNA sequencing AngII and PPE-induced AAAs in mice. Inhibition of H19 inhibits aneurysm formation in AngII-and PPE-AAA mouse models, lowldlr Yucatan mini pigs, samples from AAAs patients, and low-ldlr Yucatan mini pigs (Li et al, 2018). H19 is markedly elevated in advanced AAAs.…”
Section: H19mentioning
confidence: 90%
“…Few studies have examined the function of lncRNAs in the onset and progression of vascular disease. Currently, H19 is the only lncRNA associated with AAA (Li et al, 2018). Numerous studies have discovered that lncRNAs play a crucial role in the processes required to grow and spread AAA.…”
Section: Aaa and Lncrnasmentioning
confidence: 99%